Effects of thermal treatments on transformation behaviour in shape memory Cu-Al-Ni alloys - Dagdelen, F; Gokhan, T; Aydogdu, A; Aydogdu, Y; Adigüzel, O (Elsevier Science Bv, 2003)
The martensitic transformation behaviour, morphology and transition temperatures in copper-based shape memory alloys are strongly influenced by heat treatments. The effects of various quenching, up-quenching and step-quenching in a water bath 100 degreesC and in an oil bath at 200 degreesC have been studied on two shape memory Cu-Al-Ni alloys. The changes at entropy and enthalpy at the martensitic transition have been determined by means of differential scanning calorimeter (DSC) measurements. It was observed that quenching has a marked influence on the transformation temperatures. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: transformation temperature; shape memory alloys; Cu-Al-Ni; entropy; enthalpy